Septo-optic dysplasia Displasia septo-óptica - Karina de Ferran; Isla Aguiar Paiva; Daniel Luiz Schueftan Gilban; Monique Resende; Micheline Abreu Rayol de Souza; Izabel Calland Ricarte Beserra; Marilia Martins Guimarães (Arquivos de Neuro-Psiquiatria)
Septo-optic dysplasia (SOD), also referred to as de Morsier syndrome, is a rare congenital condition, characterized by two of the classic triad features: midline brain abnormalities, optic nerve hypoplasia (ONH) and pituitary endocrine dysfunction. We report 5 children with SOD, originally referred to be evaluated due to short stature, who also presented bilateral optic nerve hypoplasia, nystagmus and development delay. In 4 of the patients, we identified neuroimaging abnormalities of the hypothalamo-pituitary axis such as anterior pituitary hypoplasia (3/5), ectopic posterior pituitary (4/5), thin or absent stalk (3/5) and empty sella (1/5). We also encountered diverse pituitary deficiencies: growth hormone (3/5), adrenocorticotropic hormone (3/5), thyroid-stimulating hormone (2/5) and antidiuretic hormone (1/5). Only one child presented intact pituitary function and anatomy. Although rare, SOD is an important cause of congenital hypopituitarism and it should be considered in children with optic nerve hypoplasia or midline brain abnormalities for early diagnosis and treatment. A displasia septo-óptica (DSO, síndrome de Morsier) é uma condição congênita rara definida por dois critérios da tríade: defeitos de linha média, hipoplasia de nervo óptico e insuficiência hipotálamo-hipofisária. Descrevemos 5 casos de DSO, encaminhados por baixa estatura, com hipoplasia dos nervos ópticos, nistagmo e atraso global do desenvolvimento. Destes, 4 possuem alteração na ressonância magnética de sela túrcica e insuficiência hipotálamo-hipofisária, tendo sido observada adeno-hipófise hipoplásica (3/5), neuro-hipófise ectópica (4/5), haste afilada/ausente (3/5) e sela vazia (1/5), além de déficit dos eixos somatotrófico (3/5), adrenocorticotrófico (3/5), tireotrófico (2/5) e do hormônio antidiurético (1/5). Apenas um paciente não apresenta alteração anatômica ou funcional do eixo hipotálamo-hipofisário. Embora rara, a DSO é causa importante de hipopituitarismo congênito, devendo ser considerada em crianças com hipoplasia de nervo óptico ou defeito de linha média para seu diagnóstico e tratamento precoces, evitando seqüelas graves.